Relationship between health literacy, knowledge of cervical cancer, knowledge of pap smear and attitude towards pap smear among Malay Muslim women attending pre-marital course / Nurul Nadia Baharum - Baharum, Nurul Nadia (2019)
Cervical cancer is a preventable disease. However, despite good awareness of the disease among women in Malaysia, the pap smear uptake is still poor. Measuring health literacy level could explain this discrepancy. This study aims to determine the relationship between health literacy, level of knowledge of cervical cancer and Pap smear with attitude towards Pap smear among women attending pre-marital course. A cross sectional study was performed in three randomly selected Pejabat Agama Islam Daerah (PAID) that organised pre-marital courses. All Malay Muslim women aged 18 to 40 years old attending the pre-marital course during the study period were recruited while non-Malaysian, illiterate, and had hysterectomy were excluded. Validated self administered questionnaires used were European Health Literacy Questionnaire (HLSEU-Q16 Malay) and Knowledge, Attitude towards cervical cancer and pap smear questionnaire and were administered on the first day of the two-day course. The mean percentage score was calculated, with higher scores showed better outcomes. Further analysis applied multiple linear regression to measure the relationship of independent variables with attitude towards Pap smear. Total of 417 participants recruited with mean age of 24.9 ± 3.56 years old. Prevalence of awareness of cervical cancer was 91.6% (n=382, 95% CI: 89.0%, 94.2%), mean percentage score of knowledge of cervical cancer 74.7% ± 7.6 SD. Prevalence of awareness of Pap smear was 59.0% (n=246, 95% CI: 54.2%, 63.8%), mean percentage score of knowledge of Pap smear 80.2% ± 6.5 SD. The health literacy mean score was 13.3 ± 3.6 SD, with minimum score 0, maximum score 16. The mean percentage score of attitudes towards Pap smear was 64.8% ± 9.3SD. Multiple linear regression analysis demonstrated significant linear relationship between health literacy (p=0.047) and knowledge of Pap smear (p<0.001) with attitude towards Pap smear. A higher health literacy with high knowledge of Pap smear improves the attitude towards Pap smear. Pre-marital course is an opportunistic platform dissemination and intervention to improve information appraisal regarding cervical cancer and Pap smear screening.